Whanaungatanga and social capital: experiences of Māori unpaid caregivers during the COVID-19 pandemic - Uekusa S; Phibbs S; Matthewman S; Tamaira M; Barnard T; Stephens C; Alpass F (SAGE Publications, 2026)
This article examines the experiences of Māori unpaid caregivers during the COVID-19 pandemic, focusing on whanaungatanga (relationships, kinship) as crucial components of social capital. Through 35 in-depth interviews conducted between May 2023 and April 2024, we explore how the disruption of familial gatherings due to lockdowns impacted participants in our study, but also how digital technology and strong whānau (family) and community connections helped mitigate these effects. The study situates whānau experiences within Bourdieu’s capital theory, illustrating how Māori cultural values act as both social and cultural capital embedded in whanaungatanga, reinforcing unpaid caregivers’ adaptability. Despite challenges posed by the pandemic, participants utilised digital forms of cultural capital to maintain whanaungatanga, while some experienced reconnections with whānau, deepening their cultural and emotional bonds. This article contributes to the understanding of Māori unpaid caregiving practices during crises, offering insights into intersections between different forms of capital in times of disruption.
Keywords: cultural capital; pandemic; social capital; unpaid caregivers; whānau caregivers; whanaungatanga